The Influence of Defecation Behavior, Drinking Water Sources, and Handwashing Habits N Stunting in the Work Area of Merek Community Health Center - Perangin-angin, Susanti Br; Sembiring, Haesti; Manik, Erba Kalto (Syntax Corporation Indonesia, 2025)
This research was conducted due to the low motivation of the community in the work area of the Brand Health Center to build CTPS facilities, healthy latrines, and clean water management systems. The limited ownership of these facilities is a major factor contributing to the failure to achieve key indicators of STBM, such as the high prevalence of open defecation. This study employed an action research design with an observational approach and educational interventions. The process began with problem identification through observation and surveys, followed by community education and assistance in constructing CTPS facilities, managing clean water, and building latrines. Before the intervention, residents in several villages within the Brand Health Center area were less motivated to develop CTPS facilities, clean water systems, and latrines, due to low knowledge, financial constraints, and limited awareness of the importance of a clean and healthy lifestyle. After direct education and mentoring, there was an increase in motivation and independent efforts by the community to establish these facilities. The results showed improvements such as a reduction in open defecation, the adoption of handwashing with soap, and better practices in managing drinking water. To ensure sustainability, it is recommended that regular supervision and continued assistance be provided so that these achievements remain consistent in the long term.